Biaya dan Manfaat pada Penerapan Ekonomi Sirkular dalam Pengelolaan Sampah - Hilmiawan, Gigih Aulia; pratiwi, Nurna Pratiwi (Jurnal Akuntansi, 2023)
This study aims to identify the costs and benefits of waste management in implementing a circular economy in Panggungharjo Village Government. This research applies research methods with a qualitative approach. Qualitative research to understand human or social phenomena. This is done by creating detailed and complex images that can be expressed through words. In this research plan, the data collection methods to be used are observation, interviews and documentation. In this study, using a phenomenological study development approach, with the application of a coding data analysis model developed by Strauss and Corbin. The coding process is divided into three categories, namely open coding, pivoted coding, and selective coding. The results of research on the costs and benefits of waste management, researchers succeeded in describing the reality that occurs in waste management in village governments. In determining the meaning of the results of the study, three core categories were obtained, namely decoupling in determining the existence of village policies, costs and benefits in implementing a circular economy in waste management and improving public services.